Miniature of the Pancasila Family: An Analysis of Interfaith Marriage Practices among the Tengger People and Their Implications for Indonesian Family Law - Masrukhin; Lutfi Rahmatullah; Ahmad Suhendra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Abstract Interfaith marriage in Indonesia remains a deeply contested issue within legal and religious perspectives, particularly following the enactment of Law Number 1 of 1974 and the Supreme Court Circular Letter Number 2 of 2023, both of which reinforce prohibitive norms and impose stricter administrative procedures. In contrast to these state-centered regulations, the Tengger indigenous community on the slopes of Mount Bromo treats interfaith marriage as a legitimate tradition aimed at sustaining social harmony. While existing studies have predominantly focused on normative legal debates and theological controversies, limited attention has been paid to local cultural practices that offer alternative, lived models of coexistence. This gap is crucial because indigenous experiences provide socio-legal insights that are often overlooked in state-centered analyses. Addressing this gap, this article explores how interfaith marriage is understood and practiced within Tengger customary law, examines its implications for Indonesia’s national family law framework, and analyzes the idea of the “miniature Pancasila family” as an expression of legal pluralism at the community level. Drawing on qualitative socio-legal research conducted in Ngadas, Wonokerto, and Ngadisari, the findings show that communal harmony is preserved through the waralaga custom and the philosophical principle of rukun, alongside pragmatic administrative strategies, such as “temporary conversion”, employed to meet state requirements. These insights suggest that Indonesia’s family law could benefit from more contextual and pluralistic approaches that resonate more closely with Pancasila’s foundational values. Abstrak Artikel ini menjelaskan bahwa fenomena perkawinan beda agama di Indonesia terus memicu perdebatan hukum dan keagamaan, terutama sejak berlakunya Undang-Undang Nomor 1 Tahun 1974 serta Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023 yang menegaskan larangan dan pengetatan administrasi. Berbeda dengan itu, komunitas adat Tengger di lereng Gunung Bromo justru memandang perkawinan beda agama sebagai tradisi yang sah dan dapat menjaga kerukunan sosial. Kajian sebelumnya masih berfokus pada perdebatan normatif-teologis, sehingga kurang memberi perhatian pada praktik budaya lokal yang menawarkan model koeksistensi alternatif. Kekurangan ini penting karena pengalaman hidup komunitas adat memberikan dinamika sosiolegal yang jarang terungkap dalam analisis yang berpusat pada negara. Artikel ini mengkaji bagaimana perkawinan beda agama dipahami dan dijalankan dalam adat Tengger, implikasinya terhadap hukum keluarga nasional, serta bagaimana konsep “keluarga miniatur Pancasila” mencerminkan pluralisme hukum pada tingkat komunitas. Berdasarkan penelitian kualitatif sosio-legal di Ngadas, Wonokerto, dan Ngadisari, temuan menunjukkan bahwa harmoni dipelihara melalui adat waralaga dan filosofi rukun, sementara strategi administratif seperti “konversi sementara” digunakan untuk memenuhi syarat negara. Temuan ini menegaskan perlunya regulasi keluarga yang lebih kontekstual dan pluralistik sesuai nilai Pancasila.